2022
DOI: 10.31234/osf.io/fdr3u
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electrophysiological evidence for a Whorfian double dissociation of categorical perception across two languages

Abstract: Languages vary considerably in how they group objects into categories. For example, the word taza in Spanish can refer to either cup or mug in English, whereas glass can refer to either copa or vaso – two different types of glasses –, in Spanish. It is still debated whether such language distinctions cause differences in early perceptual processing between speakers of different languages. Here, for the first time, we test the effects of terminology on pre-attentive indices of categorical perception symmetrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The authors found a right visual field categorical perception effect both immediately after learning and after consolidation, affecting the amplitude of early peaks of ERPs (P1, N1, and N2), elicited by a circular display of objects featuring either a within-or cross-category target. This result provides strong support for a causal role of language terminology in early categorical perception, since it was obtained in a learning paradigm when participants had no preexisting knowledge of the labels or the function of the objects presented (a fundamental difference from participants tested by Casaponsa et al, 2024).…”
Section: An Overview Of the Contributions In The Special Issuementioning
confidence: 56%
See 3 more Smart Citations
“…The authors found a right visual field categorical perception effect both immediately after learning and after consolidation, affecting the amplitude of early peaks of ERPs (P1, N1, and N2), elicited by a circular display of objects featuring either a within-or cross-category target. This result provides strong support for a causal role of language terminology in early categorical perception, since it was obtained in a learning paradigm when participants had no preexisting knowledge of the labels or the function of the objects presented (a fundamental difference from participants tested by Casaponsa et al, 2024).…”
Section: An Overview Of the Contributions In The Special Issuementioning
confidence: 56%
“…In an oddball design manipulating the degree of matching between prime animation and target picture, the authors found that target pictures matching the animation in terms of object shape, but not transitivity, elicited a reduced P300 effect as compared to pictures matching the animation in terms of transitivity but not object shape (the P300 indexes spontaneous shifts of attention towards an infrequent, salient stimulus). A further test involving an oddball paradigm (following the same principle as that used by Casaponsa et al, 2024) showed that transitivity deviants elicited a vMMN modulation whereas object shape deviants did not. The authors concluded that implicit learning of a novel grammatical morpheme can immediately alter preattentive visual processing.…”
Section: An Overview Of the Contributions In The Special Issuementioning
confidence: 96%
See 2 more Smart Citations
“…Online Versus Offline Effects on Perception Many studies have found CP for categories such as colors, familiar objects, or familiar animals, also comparing speakers of different native languages or bilinguals (Athanasopoulos et al, 2010;Boutonnet et al, 2013;Casaponsa et al, 2022;Drivonikou et al, 2007;Gilbert et al, 2006;Regier & Kay, 2009;Thierry et al, 2009;Witzel & Gegenfurtner, 2016). These categories are based on extensive prior experience, and language may have shaped preexisting mental representations of these categories in long-term memory, which makes it difficult to distinguish between online and offline effects.…”
Section: Background Literaturementioning
confidence: 99%